Bawean Island Community Survival Strategies During the COVID-19 Pandemics - Singgih Susilo; Novia Fitri Istiawati; Ifan Deffinika; Budijanto Budijanto (Journal of Indonesian Social Sciences and Humanities, 2021)
This study aims to examine the strategies and actions of the people of Bawean Island in meeting food needs during the COVID-19 pandemic by using Max Weber’s theory of action. Extracting information was carried out using participatory observation techniques and in-depth interviews and was supported by documentation and analysis using inductive use. The results showed that there were two strategies and actions, namely: saving on food needs and limiting household expenses. Saving on food needs is done by changing the consumption pattern of side dishes. People are looking for replacement side dishes, for example; People who are accustomed to consuming fresh sea fish for a week in a row, have started to replace them with tofu, tempeh and rencek fish. The savings were made because during the pandemic, the traffic flow from Bawean Island to Java (Gresik) was not smooth, causing foodstuffs to increase in price and scarcity. Restrictions on household expenditure are carried out by reducing household spending and only focusing on spending on food, health, electricity and fuel oil needs. These two strategies can save household food and shopping needs, before the pandemic it was usually IDR 150,000 to IDR 70,000-80,000 per day. Furthermore, the actions taken by the people of Bawean Island, namely continuing to work at the main job and working side jobs to increase income. People who choose to keep working in the main job feel that they cannot do anything other than survive in this job, this is done by many furniture traders and entrepreneurs who in the end, because there are no customers, are forced to use their savings for their daily needs. People who choose to work side-by-side are more based because they do not have savings funds and have to increase their income, the people who work a lot on the side in this research are the fishermen.